Strategi Pengembangan UMKM Sate Kelinci di Lokawisata Baturraden Kabupaten Banyumas: Strategi Pengembangan UMKM Sate Kelinci di Lokawisata Baturraden Kabupaten Banyumas - WARDONI, ILHAM; Setianto, Novie Andri; Wakhidati, Yusmi Nur; Dharmawan, Budi; Lestari, Sri (Jurnal Peternakan Nusantara, 2023)
Processed food from rabbit meat has great potential as a healthy food for people. High protein and low fat is the superiority from rabbit meat, but food from rabbit meat is not familiar as chicken meat. There are several processed food from rabbit meat in Banyumas, one of them which is UMKM Rabbit Satay at the Baturraden Lokawisata. The purpose of this research is to find out strategy for development for UMKM Rabbit Satay. This research was conducted from September to October 2022. The result of this research using SWOT analysis showed that position of the UMKM Rabbit Satay at the Baturraden Lokawisata is in V position (Hold and Maintenance). Meaning is necessary to maintain good performance and fixed some bad performance. The strength and opportunities is the highest score of 3.444. This means that beautiful view can make consumer to enjoy it with some food, high protein content needs to be advertising or make a banners, lots of visitors have a healthy lifestyle make opportunities can be combined with discount prices or can increase the number of orders